THE EFFECT OF MARKET ORIENTATION AND ENTREPRENEURIAL MARKETING ON MARKET PERFORMANCE AND BUSINESS SUSTAINABILITY OF BAG CRAFT MSMES - Putranto, Eko Aji; Sarma, Ma'mun; Munandar, Jono Mintarto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
This study aims to investigate the effect of market orientation and entrepreneurial marketing on market performance, as well as the effect of entrepreneurial marketing and market performance on business sustainability of bag craft micro, small, and medium enterprises (MSMEs). This study was conducted using a descriptive-quantitative method, with eighty bag craft entrepreneurs serving as research participants. Questionnaires were used to collect data from the research participants over a period of thirty days. The data was analyzed using descriptive analysis and the structural equation modeling-partial least square (SEM-PLS). The results show that the market orientation and entrepreneurial marketing have a significant effect on the market performance, and so does the market performance on the business sustainability. However, the entrepreneurial marketing has no significant effect on the business sustainability. These findings imply that both market orientation and entrepreneurial marketing are essential determinants of the market orientation. Thus, the bag craft entrepreneurs must address these issues.JEL: M30, M31.